Effect of International Crude Oil Prices and Production on Nigerian Economic Growth (1974-2023) - Sule-Iko, Sadeeq Sani Sami; Nwoye , Ifeoma May (West Science Journal Economic and Entrepreneurship, 2025)
This research analyzes the influence of Crude Oil Price (COP) together with Crude Oil Price Volatility (COPV) and Crude Oil Production (COPR) on Nigerian economic performance through their impact on Real Gross Domestic Product (RGDP) and Gross National Product (GNP). The research utilizes FDI as a control parameter to measure how external investment affects the results. The study analyzes the long-term relationships between variables using the Autoregressive Distributed Lag (ARDL) Bounds Test for Cointegration and it assesses short-term patterns through the Error Correction Model (ECM). Economic data shows that crude oil price presents the strongest positive relationship with Nigerian economic growth which has substantial effects on RGDP (0.1809 p=0.0120) alongside GNP (0.8197 p=0.0066). Crude oil production shows minimal effects on national income and GNP (0.6446, p=0.3260) while price volatility produces just a weak impact on economic performance. The statistical tests establish that FDI has no significant impact on growth because foreign capital fails to generate sustainable development outcomes. Analysis of the error correction term reveals that economic shocks get corrected in 62.53% of cases for RGDP segments and 56.16% for GNP segments each year thus showing moderate adjustment speed. The research shows that Nigeria depends primarily on crude oil price changes rather than production quantity or price stability which emphasize the need for diversification. Policy recommendations include improved financial policies, enhanced production efficiency, and oil price stabilization programs